Signs of Fragmentation in Inter-Religious Relationships in the North and East of Sri Lanka: An Obstacle or a Catalyst to Socio-Cultural and Economic Advancements - Paul Rohan, J.C. (Federation of Global Tamils, University of Toronto, Scarborough, 2025)
The North and East of Sri Lanka, long devastated by civil war, remain at the center of the country’s fragile recovery process. These regions, home to Tamil, Muslim, and Christian communities, now face a new challenge: rising inter- religious fragmentation. While Sinhala - Buddhist dominance defines the national sphere, localized tensions between Hindu, Muslim, and Christian groups increasingly obstruct social harmony and economic reconstruction. During the war, Hindus and Christians shared solidarity in resisting Sinhala monopolization. Since 2009, however, Hindu revivalist movements such as Siva Sena, Urudhra Sena, etc., have sought Saivite dominance in the North, often marginalizing other religious institutions, while Muslim identity politics in the East has intensified around mosque construction and land disputes. Incidents in Kattankudy, Trincomalee, and Jaffna illustrate how competition over sacred space fuels mistrust, sometimes erupting in violence. The 2019 Easter Sunday bombings further deepened suspicion, exacerbating divisions between Tamil and Muslim communities. These tensions carry material consequences. Diaspora remittances, critical for post-war recovery, are increasingly channelled towards religious construction rather than infrastructure, education, or livelihoods. NGOs report that inter-religious rivalry undermines cooperative livelihood schemes, particularly among women, while shared cultural practices and festivals that once fostered unity are eroding. Such patterns involve in risk of shifting the conflict paradigm from ethnicity to religion, perpetuating instability. This paper argues that fragmentation, if left unaddressed, will remain a major obstacle to recovery. Yet, if engaged constructively through inclusive governance, interfaith dialogue, and purposeful Diaspora engagement, it may also become a catalyst for building pluralist solidarity, socio-cultural resilience, and sustainable economic advancement in the North and East.
Keywords: Inter-religious fragmentation; Majoritarianism; Post-war recovery; Diaspora engagement; Religious pluralism